Social protests in the urban development of the city of Puno - Abarca Macedo, Flavio Demetrio; Tapia Cruz, Mauro Octavio; Apaza Ticona, Jorge; Alemán Cruz, Leoncio Efraín (Street Art & Urban Creativity, 2025)
The research analyzes the impact of social protests in Puno, Peru, focusing on the perceptions of residents and authorities. This phenomenon, driven by political, economic and social factors, affects commerce, transportation and citizen security. Through interviews and focus groups, four impact categories were identified: urban development, commerce, transportation and security. Some see protests as tools of protest, while others perceive them as causing chaos. In commerce, there is a decrease in sales and changes in consumption patterns. In transportation, protests generate disruptions and the need for alternatives. Citizen security is affected by an increase in the perception of insecurity and cases of violence. Additionally, criticism of the law enforcement response highlights the excessive use of force. The results reflect the complexity of the experiences related to the protests in Puno.